Sikap Terhadap Pembiayaan Syariah di Libya Dan Italia: Sebuah Analisis Isi Terhadap Artikel Gait & Worthington (2015) Dan Opromolla (2012) - Alexander Joseph Ibnu Wibowo (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2018)
Nowadays there are relatively few studies that have compared consumer attitudes to Islamic finance in developed and developing countries. This study aims to analyze differences in attitudes towards Islamic finance between bank consumers in developed country (Italy) and developing country (Libya), including identifying various antecedents of attitudes to seeking financing by bank consumers in both countries. For this reason, we conducted an exploratory study through a content analysis of two scientific journal articles. Specifically, we systematically reviewed two scientific journal articles that discussed the bank's attitude towards Islamic finance. The first article was written by Gait and Worthington (2015) and the second article was written by Opromolla (2012). We found that the study of Gait et al. (2015) succeeded in identifying four determinants of consumer attitudes toward Islamic finance, namely community service, profitability, religion, and unique services. In addition, religion and community service are the most important positive attitudes that determine the use of Islamic finance methods by retail consumers in Libya. On the other hand, the Opromolla study (2012) aims to analyze the suitability of Islamic banking with the Italian banking system. Through a practical analysis of experience in financial services in Italy, it was found that although Italy provides a conducive and flexible legal environment and supporting banking laws and regulations, Islamic banks are not yet established in Italy. For this reason, we need a way to adjust (reconcile) Islamic banking with EU regulations and the Italian banking system. In summary, the slow progress of Islamic banking in Italy is likely to be answered through the findings of empirical studies conducted by Gait and Worthington (2015).